Kingdom of the Netherlands-Netherlands : Detailed Assessment of Standards and Codes. (IMF Staff Country Reports; Country Report, 2004)
This Detailed Assessment of Standards and Codes on the Kingdom of the Netherlands-Netherlands reviews Basel Core Principles for effective banking supervision. Because of the highly developed nature of the Netherlands insurance market and the large exposure to international financial activities, this assessment comments on both the essential and advanced criteria, underpinning each core principle. The authorities in the Netherlands are actively pursuing a number of legislative and supervisory initiatives that hold the potential to materially improve the level of observance.